Income Volatility and Residential Mortgage Delinquency : Evidence from 12 EU Countries - Luis Diaz-Serrano (Institute for the Study of Labor (IZA), 2004)
We investigate the socio-economic determinants of mortgage delinquency in 12 EU countries and observe that income volatility significantly increases the mortgage delinquency risk. This pattern even holds for borrowers with higher-income profiles if volatility in income is high enough. From this result we can draw the following conclusions: i) mortgage protection insurance policies might be failing to cover those borrowers most in need; ii) the existence of credit market imperfections, and; iii) the inability for a number of borrowers most at income risk to accumulate precautionary savings in order to meet mortgage payments when shocks in income arise.
Keywords: J0; R0; D1; 330; income volatility; mortgage delinquency; mortgage insurance; homeownership; payment-to-income ratio; credit market imperfections; Hypothek; Kreditrisiko; Einkommen; Volatilität; Kreditsicherung; Schätzung; Wohneigentum; EU-Staaten